PLoS Medicine Issue Image | Vol. 21(4) May 2024 (PLOS Medicine, 2024)
Approximately 1.2 million people in the UK experience severe–to–profound hearing loss, for which cochlear implants are an effective treatment. However, only a small proportion of potentially eligible individuals receive cochlear implantation in the UK. In this issue, Chloe Swords and colleagues explore how referral patterns for cochlear implantation vary across the UK according to ethnicity and socioeconomic measures, in a multi-centre study including over 6000 participants. Image Credit: Brett Sayles, Pexels